Evaluation of ski boot fitting characteristics by means of different pressure distribution measurements - Pinter, M.; Eckelt, M.; Schretter, H. (Procedia Engineering, 2010)
To make the boot-fitting measurable, there was the attempt to conduct pressure measurements between a ski boot and a subject's foot as well as the lower leg. Therefore pressure distribution measurements within three different ski boots, which were worn by six subjects, were executed with two different measurement setups. The study at hand is the first which examines the pressure distribution at the dorsum of foot within a ski boot. After each measurement the subject was interviewed about the fitting to find correlations. The advantages and disadvantages of every measuring system in use became obvious. The tests showed that it is necessary to measure the pressure of a wide spread area of the foot, instead of points, to ensure that there is a steady pressure over the whole area. You can also infer from the results which boot feels painful to the subject, as well as how the pressure distribution should look like within the boot. So it would be possible to shorten the search of the customer to find the best fitting boot or research how the pressure distribution within the ski boot behaves under load.